The Beast and the end-time events - Solomon, Zomaya S. (Solomons Computer Designs, LLC, 2002)
Introduction. The beast's beginnings -- Daniel's "little horn" -- Present developments -- Transfer of God's throne -- The Lord's returning -- Satan: His origin and his finale -- The rapture of the Church -- The indivisible Church -- Glorious events in Heaven -- The rise of the Beast -- The northern invasion -- The demise of apostasy -- The great tribulation period -- God's final summons -- The dreadful events on earth -- Who is the Beast? -- The Millennial kingdom -- The Great White Throne and beyond . Appendix A: Method of interpretation -- Appendix B: Symbolic terms interpereted -- Appendix C: A list of some new itnerpretations -- Appendix D: Terrorism strikes America